Intensitas serangan Spodoptera frugiperda J.E. Smith pada pertanaman jagung di kecamatan Mendo Barat kabupaten Bangka - Apriyadi, Rion; Marlinda, Riska Yuni; Aini, Sitti Nurul; Prayoga, Gigih Ibnu (Universitas Bangka Belitung, 2023)
Fall Armyworm (Spodoptera frugiperda J.E. Smith) is a new pest species in Indonesia which has the potential to attack corn plantation in Mendo Barat District because it has the highest harvested corn area in Bangka Regency. The purpose of this study was to determine the attack intensity, Symptom Characteristics and distribution of S. frugiperda on corn plantations in Mendo Barat District, Bangka Regency. The study had been conducted in November 2019 to February 2020 using the observation method. Study sites and sampling techniques was carried out by using purposive sampling technique. The results showed S. frugiperda larvae had the same characteristics as those found in Africa, namely the inverted Y pattern on the head, four black dots on the eighth dorsal segment, thick bands on the lateral part and three bright lines on the upper body. Symptoms of an attack in the early vegetative phase of corn were transparent holes in the leaves and shoots, while in the reproductive phase were damaged cob and corn kernels. The number of caterpillars, the highest number of plants attacked and damaged were found in Petaling Banjar Village by 55% intensity of severe attacks. The intensity of relative damage was at 31.6%. Most of the plants attacked and damaged by S. frugiperdawere found mostly in the tasseling and silking (R1) phase and monoculture planting systems. We conclude the S. frugiperda attacked the corn plants in Mendo Barat District and caused various kinds of damage in accordance with the growing stage of corn plants.